A identidade feminina em Clarice Lispector: tradição x descentramento - Junior, Arnaldo Franco [UNESP] (My University, 2004)
This article discusses how the conflict between decentered subjectivity and the bourgeois identity constitutes the female character in Clarice Lispectorś work, and how it serves the questioning of patriarchal and modern traditions.

Neste artigo, estudaremos como o conflito entre a subjetividade descentrada e a identidade burguesa constitui a personagem feminina na obra de Clarice Lispector, prestando-se, simultaneamente, ao questionamento da tradição patriarcal e da tradição moderna.
Feminine identity in Clarice Lispector: tradition vs. decentering
Keywords: Identity; Kitsch; Representation; Subject; Tradition; Woman